Comparison of Outcomes of Kidney Transplantation From Extremely Low Body Weight ≤5kg Versus Larger Body Weight Pediatric Donors - Peng, Jiawei; Dai, Helong; Zhang, Hedong; Yu, Shaojie; Xie, Xubiao; Peng, Fenghua; Lan, Gongbin; Hu, Shanbiao; Wang, Yu; Tang, Xiaotian; Guo, Yong; Gao, Chen; et al. (Frontiers in Immunology, 2021)
Background: Kidney transplantation from donors who weigh ≤5 kg is performed at only a few transplant centers owing to the high complication and low graft survival rates associated with this approach. Methods: We retrospectively compared the results of kidney transplantation at our center between January 2015 and December 2019 based on the following pediatric donor criteria: donor body weight ≤5 kg (n=32), 5 kg< donor weight ≤20 kg (n=143), and donor weight >20 kg (n=110). We also perform subgroup analysis of kidney transplantation outcomes from ≤5 kg donors, using conventional (dual separate and classic en-bloc KTx) / novel (en-bloc KTx with outflow tract) surgical methods and allocating to adult/pediatric recipients. Results: The death-censored graft survival rates from extremely low body weight ≤5kg at 1 month, and 1, 3, and 5 years were 90.6%, 80.9%, 77.5%, and 73.9%, respectively, which were significantly lower than that from larger body weight pediatric donors. However, the 3-, and 5-year post-transplantation eGFRs were not significantly different between the pediatric and adult recipient group. The thrombosis (18.8%) and urinary leakage (18.8%) rates were significantly higher in the donor weight ≤5 kg group. Compared with 5 kg< donor weight ≤20 kg group, donor weight ≤5kg group was at elevated risk of graft loss due to thrombosis (OR: 13.4) and acute rejection (OR: 6.7). No significant difference on the outcomes of extremely low body weight donor kidney transplantation was observed between adults and pediatric recipients. Urinary leakage rate is significantly lower in the novel operation (8.7%) than in the conventional operation group (44.4%). Conclusions: Although the outcomes of donor body weight ≤5kg kidney transplantation is inferior to that from donors with large body weight, it can be improved through technical improvement. Donors with body weight ≤5 kg can be considered as an useful source to expand the donor pool.